Inclusion of Children with Intellectual Disability in Early Childhood Education in Saudi Arabia: Impact of Teacher Characteristics - Alanazi, Adel; Alhazmi, Adnan (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: The practice of inclusive education in mainstream classrooms has gained momentum worldwide in recent years. This situation has attracted the interest of researchers in equal measures, with the main focus being directed at the impact of teacher attitudes toward inclusive education. The previous studies have mainly focused on inclusive education in primary and secondary education environments in the Western world while paying no attention to early childhood education in developing countries like Saudi Arabia. Aim: This study fills this knowledge gap by investigating the impact of teacher characteristics on the attitudes toward the inclusion of children with intellectual disabilities in early childhood education in Saudi Arabia. Methods: Data were collected through a web-based survey. Statistical analysis was conducted using SPSS to generate descriptive statistics and correlations. Results: There were statistically significant relationships between acceptance of inclusion of learners with IDs and all the independent variables; age (p=0.000), gender (p=0.021), training (p=0.000), professional role (p=0.015), knowledge (p=0.000) and experience (p=0.000). Conclusion and Recommendations: Early childhood education teachers in Saudi Arabia should receive training on special needs to attain knowledge and experiences in dealing with learners with IDs in inclusive environments.